SERUM MYELOPEROXIDASE, MALONDIALDEHYDE, ALPHA-SYNUCLEIN LEVELS IN PATIENTS WITH EPILEPSY - ÅžimÅŸek, Fatma; Ceylan, Mustafa; AÅŸkÄ±n, Seda; KÄ±zÄ±ltunÃ§, Ahmet (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Â Processes such as neurodegeneration, hypoxia, blood brain barrier dysfunction and oxidative changes are effective for epileptogenesis.There is no non-invasive biomarker that can be used in the follow-up of patients with epilepsy, which is a neurodegenerative disease.Objective: In our study, it was aimed to investigate the relationship between inflammatory, oxidative, neurodegenerative processes, and antiepileptic use in patients with epilepsy.Methods: The groups were formed from the patients who were followed up in the epilepsy outpatient clinic between April 2019-June 2019, and the age-gender-matched control group.The study included 30 patients and 30 healthy volunteers. Venous serum samples were collected from groups to study myeloperoxidase, malondialdehyde and alpha-synuclein.Results: The levels of myeloperoxidase and malondialdehyde were higher in the control group and this difference was statistically significant (p=0.003, p<0.001). The level of Î±-syn was higher in the epilepsy group and there was no statistically significant difference between the two groups (p=0.52). There was a positive correlation between the Î±-syn level and disease duration and as the disease duration increased, the level of Î±-syn increased (r=0.379, p=0.03).Conclusion: Although the Î±-syn level increases with the duration of the disease in epilepsy patients, it is not a suitable parameter for use as a biomarker in the follow-up.